2017
DOI: 10.1515/meceng-2017-0026
|View full text |Cite
|
Sign up to set email alerts
|

Modal Analysis of Laminated “CAS” and “CUS” Box-Beams

Abstract: In the paper, the authors discuss the numerical and experimental modal analysis of the cantilever thin-walled beams made of a carbon-epoxy laminate. Two types of beams were considered: circumferentially asymmetric stiffness (i.e., CAS) and circumferentially uniform stiffness (i.e., CUS) beams. The layer-up configurations of the laminate were chosen to get a vibration mode coupling effect in both analysed cases. The aim of the paper was to perform the numerical and experimental modal analysis of the composite s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…A total of 9227 nodes and 7170 elements were obtained for this spring model. In order to identify the normal mode of the coil spring, FE modal analysis was performed using the Lanczos method [26]. One end of the coil spring was fixed with a rigid body and fixed boundary conditions to ensure that there was no movement allowed.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 9227 nodes and 7170 elements were obtained for this spring model. In order to identify the normal mode of the coil spring, FE modal analysis was performed using the Lanczos method [26]. One end of the coil spring was fixed with a rigid body and fixed boundary conditions to ensure that there was no movement allowed.…”
Section: Methodsmentioning
confidence: 99%
“…These interactions enabled the simulation of a permanent connection of both elements. The number of elements was assumed based on existing knowledge, such as [ 21 , 22 ]. The convergence of the model was investigated numerically, by selecting the size of the elements used.…”
Section: Finite Element Methods (Fem)mentioning
confidence: 99%
“…The Lanczos method was used for solving the eigenvalue problem, to determine the eigen-frequencies and corresponded mode [ 23 ]. It is a commonly used method that was successfully presented in [ 22 ]. Numerical studies were carried out in the Abaqus environment, where the eigenvalue problem was determined for all ana lysed variants.…”
Section: Finite Element Methods (Fem)mentioning
confidence: 99%
“…It has been concluded that the bending–torsion coupling effect needs to be considered in a one-dimensional model because this coupling can have a considerable effect on laminates with lamina orientations other than and degrees. Gawryluk et al [ 12 ] conducted a numerical and experimental modal analysis of laminated thin-walled beams, where a flapwise bending with torsion coupling effect or a flapwise–chordwise bending coupling effect took place. Circumferentially asymmetric stiffness and circumferentially uniform stiffness beams are analyzed.…”
Section: Introductionmentioning
confidence: 99%